Comovement in Anomalies between the Australian and US Equity Markets. (12th December 2018) - Chiah, Mardy; Gharghori, Philip; Zhong, Angel
Abstract: This study examines the comovement between eight prominent Australian asset pricing anomalies and their corresponding US counterparts. It confirms the continued existence of these anomalies in Australia and finds that these anomalies do not co‐move with their US counterparts. Given the conflicting findings in prior research on the integration or segmentation of the Australian and US equity markets, this study adds to the body of evidence supporting segmentation.